Effect of calcium on dry matter production and mineral composition of millets plant (Pennisetum americanum (L.) K. Schum.) - França, A.F.; Haag, H.P.; Carmelo, Q.A.C. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1987)
An experiment was conducted under greenhouse conditions to check the effect of different levels of calcium on the production of dry matter, and on the mineral composition of millet during 38 days. The following treatments were applied: 0, 50, 100, 150, 200, 250 and 300 ppm of calcium in the nutrient solution. The plants were harvested in to young leaves, old leaves, ears, and stalks, which were analyzed for N, P, K, Ca, Mg. The matter (gr.), obtained by applying different levels of calcium were: 0 1 35.5; 50 = 54.6; 100 = 63.0; 150 = 65.3; 200 = 69.6; 250 = 49.4, and 300 ppm = 55.9 gr. The authors concluded: The dry matter production obey an equation of 2º degree with a maximum production with 200 ppm of Ca in the nutrient solution. The calcium levels reduced the concentration of N, P, K, Ca and Mg in the plants. The calcium levels did not affected the minimum requeriments of the elements for the cattle nutrition.